Legal possibilities concerning restructuring of companies in business difficulties - Jelena Čuveljak; Mario Rašić (Global Labor Organization (GLO), 2017)
Since difficulties during business are an integral part of entrepreneurship, the Croatian legislative offers several restructuring models for companies who have business issues. The pre-bankruptcy agreement is available in cases when the debtor is threatened by insolvency and during this procedure, the business of the company is still managed by the existing management board. However, it is necessary that the pre-bankruptcy procedure is finished within a short deadline. The bankruptcy procedure is commenced on grounds of over-indebtedness and when in a state of incapacity to make payments, Future business is managed by the insolvency practitioner. The extraordinary administration procedure in companies of systemic importance for the Republic of Croatia is initiated in cases where large enterprises are faced with bankruptcy or pre-bankruptcy reasons. During this procedure, the business of the parent-company is conducted by the extraordinary trustee. Each of the aforementioned procedures (models) has its specifications and legal consequences for all stakeholders involved (debtor, management board and creditors). This paper will use the comparative legal research methodology to analyze the differences between them: the grounds for commencing the procedures, continuing company's business operations, deadlines and the aftermaths for the creditors and shareholders of the company. The focus of the paper will be to demonstrate that each procedure can preserve financially positive business of the companies in problems. Several legal models should enable timely restructuring of companies, which can secure the safety of sustainable businesses and help create and maintain employment, while also can reduce the risk in the finance sector connected with converting loans to poor credits. However, the success of the negotiations with relevant stakeholders, namely creditors, and the percentage of creditor's payment returns largely depend on early detection of business problems and prompt opening of appropriate proceedings.
Keywords: K22; K20; L53; 330; insolvency; bankruptcy; pre-insolvency; restructuring in bankruptcy; extraordinary administration